Determinan Kualitas Audit: Analisis Multidimensi pada Kantor Akuntan Publik di Bali - Ni Made Sunarsih; Ni Putu Shinta Dewi; Ghani Dwipayana (Jurnal Inovasi Akuntansi (JIA), 2025)
This study aims to examine the influence of auditor ethics, auditor competence, auditor experience, audit fees, and auditor motivation on audit quality. The population of this study consists of 123 auditors working at Public Accounting Firms in Bali Province registered in the 2024 IAPI Directory, with a sample size of 73 respondents obtained using the census method. The data collection technique employs questionnaires. The analytical technique used in this study is multiple linear regression. The research findings indicate that auditor ethics and auditor motivation have a positive effect on audit quality. Audit fees have a negative effect on audit quality. Meanwhile, auditor competence and auditor experience have no significant effect on audit quality. Future research is expected to develop this study by incorporating other variables that theoretically influence audit quality